O Shopping Center Iguatemi Esplanada no limite das divisas intermunicipais e as consequências na produção do espaço urbano - Forti, Marina Machado (Universidade Federal de São Carlos, 2023)
The dissertation regards the impacts from demarcation lines placement in city limits between Sorocaba and Votorantim inside Shopping Center Iguatemi Esplanada mall. Approaches the analysis of mall business as a relevant commerce model, with its characteristics and contribution for structuring of urban networks. The study encompasses brief historical facts around the relationship between Sorocaba and Votorantim and the lawsuit which questioned intercity limits. Concerning the development and production of urban space, it directed towards the impacts of taxes and collection, public management and the expansion of urban sprawl. At the end of the work, it was analyzed the unfolding of the situation of division of the mall business between two cities with the advent of the pandemic caused by COVID-19. For elaboration of this work was done a documental revision, and a bibliography revision of the Geography, promoting interdisciplinarity with areas from Law and Sociology. As a result, it was observed a formalization of the agreement and the existence of split and collaborative management between two cities, recognized by mall business.
The Iguatemi Esplanada Shopping Center in intermunicipal limits and the consequences on the production of urban spaces
Keywords: Shopping Center; Território; Sorocaba; Votorantim; Divisas Municipais; Gestão Pública; Arrecadação Tributária; Centralidade; Expansão da Mancha Urbana; Comércio; Consumo; COVID-19; Shopping Mall; Territory; City Limits; Public Management; Tax Collection; Centrality; Commerce; Consuption; Urban Sprawl Expansion; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA